Your immune system - Nourse, Alan Edward (New York : Watts, 1989)
Discusses the workings of the body's immune defense system; what happens when this system functions perfectly, too vigorously, or not at all; and current research in immunology.
Includes index.
Bibliography: p. 91.
Booklist.
Voice of Youth Advocates (V.O.Y.A.).
8.4
8.4
Keywords: Immune system -- Juvenile literature; Immunology -- Juvenile literature; Immunology; Immunology